INSTITUTIONALIZATION OF MEDIA SPACE IN THE INFORMATION SOCIETY: SOCIAL-PHILOSOPHICAL ANALYSIS - Литовченко, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In this article the social and philosophical study features institutionalization media market in the development of the information society. The analysis the features of functioning of the institution of the media, which is the active formation of an active subject of social reality.